Pengaruh Current Ratio (CR), Return On Assets (ROA) dan Debt to Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Sub Sektor Kontruksi dan Bangunan yang Terdaftar di BEI Periode 2017-2021 - Dede Verawati; N.A. Rumiasih; Desmy Riani (Komunitas Dosen Indonesia, 2024)
this study aims to determine the effect of the current ratio, return on assets and debt to equity ratio on stock prices partially and simultaneously. the number of samples used was 7 construction and building sub-sector companies registered on the IDX in the form of annual financial reports from 2017-2021. the data used is secondary data with the data collection method using the purpose sampling method. data collection techniques used documentation techniques by taking sources from the Indonesia Stock Exchange. the analytical method used in this study was multiple liniar regression using the SPSS 24 application. The results revealed that the current ratio has a negative and significant effect on stock prices. While the return on assets and debt to equity ratio has no effect on stock prices. While the silmutaneous test results have a significance value of 0,004 < 0,05, it can be concluded that simultaneously the current ratio, return on asssets and debt to equity ratio together have a significant effect on stock prices.